Comparison of Tibial and Talar Bone Density as a Function of Resection Level in Patients Undergoing Total Ankle Replacement vs Demographic-Matched Controls. Issue 4 (16th October 2019) - Harnroongroj, Thos; Volpert, Lauren; Sturnick, Daniel; Sofka, Carolyn; Ellis, Scott J.; Deland, Jonathan; Demetracopoulos, Constantine
Category: Ankle Arthritis Introduction/Purpose: Initial implant fixation is critical for long-term success of total ankle replacement (TAR). One important factor which contributes to implant stability is the quality of the surrounding bone. Previous studies characterized a decrease in bone density with increasing distance from the level of the joint in the tibia and talus in non-arthritic ankles. However, ankle arthritis affects bone density remains unclear. The objective of this study is to compare the bone density in patients with and without ankle arthritis as a function of resection level from the joint. We hypothesized that there would be no difference in bone densities at each resection level between groups and bone density would decrease with greater distance from articular surface in both groups. Methods: We retrospectively reviewed 93 end-stage ankle arthritis patients with available preoperative non-weight bearing ankle computed tomography scans (CT)(Group A) and identified another cohort of 83 patients with non-arthritic ankles as a demographic-matched control group(Group B). Patients with retained ankle hardware, history of osteomyelitis, osteoporosis, and cysts greater than 1 cm in diameter at the ankle were excluded. There was no difference in term of gender, age and body mass index (BMI) between the groups(Table 1). The ROI tool in Sectra IDS7 picture archiving and communication system (PACS) was used to calculate Hounsfield Unit (HU) values in the cancellous region of the tibia and talus around the ankle joint. Measurements were obtained on axial CTs from 6 mm to 12 mm above the distal tibial plafond, and from 1 mm to 4 mm below the talar dome. The HU measurements and percentage decrease of HU values at each level were compared between groups. Results: Patients with ankle arthritis demonstrated significantly greater bone density than the control group between 6 mm and 10 mm from the joint in the tibia. There was no significant difference in bone density between 10 mm and 12 mm from the joint on the tibia, and at all levels in the talus between groups (Table 1). In both groups, bone density decreased significantly at each successive level from the joint for the tibia and talus. In addition, the percentage decrease of HU values at each relative level was the same in both groups. Conclusion: Patients with ankle arthritis demonstrated greater bone density at 6 mm to 10 mm from the joint in the tibia compared to demographic-matched controls. The increased bone density close to the joint may stem from bone eburnation that occurs as part of the arthritic process. In TAR, a tibial bone resection between 6 mm and 10 mm may provide improved initial stability of the implant. Contrary to traditional thinking, fixation into the talus may be of less concern.